(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
درست المحاليل المتشردة منذ سنوات عديدة بشكل مكثّف نظرياً وتجريبياً، وتشكّل دراسة مواصفات هذه المحاليل فرعاً هاماً في الكيمياء الفيزيائية رغم أن الطريقة الفعّالة لمثل هذه الدراسة هي الفيزياء بفرعيها التجريبية والنظرية، ثم مقارنة النتائج النظرية مع التجريبية. أُعطيت العلاقات الأساسية وتوابع التوزيع غير المتوازنة لنظرية MSAT واستعملت توابع S في تعريف معاملات Onsager وكذلك في صيغ الناقلية الكهربائية وعدد الأنفاق ومعاملات الانتشار. نُعطي شكل معاملات Onsager في النموذج الكيميائي الواصف للمحاليل المتشردة، وتحدد جودة نظرية MSAT من خلال المقارنة مع القيم التجريبية. Few years ago the electrolyte solutions were studied intensely theoretically and experimentally. Studying the electrolyte solutions were considered an important branch of the physical chemistry. But the most active methods is the experimental and theoretical physics then comparing the results between them. The basic equations and non-equilibrium distribution function of MSAT are given. The S-functions are used to define the ONSAGER coefficients and the formulas for electrical conductivity, the transference numbers and the ambipolar diffusion coefficient. The form of the ONSAGER coefficients required in chemical models to describe associating electrolytes was stated, and the quality of the MSAT was estimated by comparison with experimental data.